Legal Protection Guarantee Agricultural Land Pawn System - Istihumaira Gobel (Estudiante Law Journal, 2021)
This study aims to determine and analyze the guarantee of legal protection for the agricultural land pawn system in Law No. 56 Prp 1960. The research method used by researchers in compiling this research is using sociological juridical research. This study uses a legal approach (state approach). The data obtained were arranged systematically so as to obtain a comprehensive picture, and by the researchers were processed using descriptive analytical techniques. As for the results of the research, namely the guarantee of legal protection for the land pawn system in Law Number 56 Prp of 1960, namely in the form of freeing ransom for the pawn system that has exceeded a period of 7 years which in that period has yielded crops